Anode catalyst layer and preparation method thereof, membrane electrode and fuel cell

By partitioning design and appropriate catalyst combination in the anode catalytic layer of the fuel cell, the anode catalytic layer has been solved, and the anode catalytic layer with high anti-reverse ability and low cost is achieved, which extends the fuel cell Service life.

CN119252951APending Publication Date: 2025-01-03CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486171.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The anode catalytic layer of the existing fuel cells is prone to reverse the phenomenon when hydrogen is undergas, resulting in corrosion of the carbon support and collapse of the catalytic layer structure, and the high amount of anti-reverse catalysts used leads to excessive cost.

Method used

The anode catalytic layer is divided into two parts near the hydrogen outlet area and the inlet area, and only the anti-reverse catalyst is added to the outlet area. A highly graphitized carbon support platinum-based catalyst and perfluorosulfonic acid resin are used to combine it with a suitable catalyst through partition design. Reduce the amount of catalyst used.

Benefits of technology

The occurrence of reverse polar phenomenon is effectively avoided, the total use of catalyst is reduced, the cost is reduced, and the durability of the membrane electrode and the service life of the fuel cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252951A_ABST
    Figure CN119252951A_ABST
Patent Text Reader

Abstract

The invention discloses an anode catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell, the anode catalyst layer is arranged on the anode side of a proton exchange membrane of the membrane electrode, and the anode side comprises a first region and a second region; the anode catalyst layer comprises a catalyst layer on the first area and a catalyst layer on the second area; the first area is close to the anode hydrogen outlet area; the second area is close to the anode hydrogen inlet area; the catalytic layer on the first region includes an anti-antipolar catalyst, a first platinum-based catalyst, and an ionomer; the catalytic layer on the second region includes a second platinum-based catalyst and an ionomer; an anode catalyst layer is divided into a catalyst layer on a first region and a catalyst layer on a second region according to a region close to an anode hydrogen outlet or a region close to an anode hydrogen inlet; the anti-reverse-pole catalyst is only added to the catalyst layer on the first area close to the anode hydrogen outlet area, so that the adding amount of the anti-reverse-pole catalyst is reduced, the cost is reduced, and meanwhile, the anti-reverse-pole effect is also realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to an anode catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell. Background Art

[0002] The anode side of the proton exchange membrane fuel cell will experience a phenomenon of hydrogen under-gassing, which will increase the anode potential and eventually cause reverse polarity. The occurrence of reverse polarity phenomenon will cause carbon corrosion reaction of the anode catalyst layer, resulting in the fall-off of platinum particles on the surface of the carbon carrier and the collapse of the catalyst layer structure, and this phenomenon is irreversible. Therefore, in order to avoid the occurrence of reverse polarity phenomenon and improve the durability of the membrane electrode, it is very important to prepare an anode catalyst layer with anti-reverse polarity ability. However, the current method for preparing the anode catalyst layer of the anti-reverse polarity membrane electrode has the problem of high use of anti-reverse polarity catalyst, which leads to excessive cost. Summary of the invention

[0003] In view of the above problems, the object of the present invention is to provide an anode catalyst layer with high anti-reverse polarity ability and low cost and a preparation method thereof, a membrane electrode and a fuel cell. The technical solution is as follows:

[0004] On the one hand, an anode catalyst layer is provided, which is arranged on the anode side of the proton exchange membrane of the membrane electrode, and the anode side includes a first region and a second region; the anode catalyst layer includes a catalyst layer on the first region and a catalyst layer on the second region; the first region is close to the anode hydrogen outlet region; the second region is close to the anode hydrogen inlet region; the catalyst layer on the first region includes an anti-reverse polarity catalyst, a first platinum-based catalyst and an ionomer; the catalyst layer on the second region includes a second platinum-based catalyst and an ionomer.

[0005] In an exemplary embodiment, the first platinum-based catalyst comprises a highly graphitized carbon-supported platinum-based catalyst.

[0006] In an exemplary embodiment, the ionomer includes a perfluorosulfonic acid resin.

[0007] On the other hand, the present invention also provides a method for preparing the above-mentioned anode catalyst layer, the method comprising:

[0008] Providing a first raw material, wherein the first raw material includes the anti-reverse polarity catalyst, the first platinum-based catalyst and the ionomer;

[0009] providing a second feedstock, the second feedstock comprising the second platinum-based catalyst and the ionomer;

[0010] Mixing the first raw material and the first solvent to obtain a first slurry;

[0011] Mixing the second raw material and the second solvent to obtain a second slurry;

[0012] Applying a first slurry to a first region to obtain a catalytic layer on the first region;

[0013] The second slurry is applied to the second region to obtain a catalytic layer on the second region.

[0014] In an exemplary embodiment, the first solvent includes one or more combinations of water or alcohol solvents;

[0015] The second solvent includes water or one or more combinations of alcohol solvents.

[0016] In an exemplary embodiment, the mixing method includes one of water bath sonication, probe sonication, shearing, ball milling or homogenization.

[0017] In an exemplary embodiment, the mixing of the first raw material and the first solvent to obtain a first slurry comprises:

[0018] The first raw material and the first solvent are mixed and then degassed to obtain a first slurry;

[0019] The mixing of the second raw material and the second solvent to obtain a second slurry comprises:

[0020] The second raw material and the second solvent are mixed and then degassed to obtain a second slurry.

[0021] In an exemplary embodiment, applying the first slurry to the first region to obtain a catalytic layer on the first region comprises:

[0022] After applying the first slurry to the first region, heat treatment is performed to obtain a catalytic layer on the first region;

[0023] The step of applying the second slurry to the second region to obtain a catalytic layer on the second region comprises:

[0024] After the second slurry is applied to the second region, heat treatment is performed to obtain a catalytic layer on the second region.

[0025] On the other hand, a membrane electrode is provided, comprising any one of the above-mentioned anode catalyst layers.

[0026] On the other hand, a fuel cell is provided, comprising the above-mentioned membrane electrode.

[0027] The invention discloses an anode catalyst layer, which is arranged on the anode side of a proton exchange membrane of a membrane electrode, and the anode side includes a first region and a second region; the anode catalyst layer includes a catalyst layer on the first region and a catalyst layer on the second region; the first region is close to the anode hydrogen outlet region; the second region is close to the anode hydrogen inlet region; the catalyst layer on the first region includes an anti-reverse polarity catalyst, a first platinum-based catalyst and an ionomer; the catalyst layer on the second region includes a second platinum-based catalyst and an ionomer; the invention divides the anode catalyst layer into a catalyst layer on the first region and a catalyst layer on the second region according to the region close to the anode hydrogen outlet region or the region close to the anode hydrogen inlet region; the anti-reverse polarity catalyst is added only to the catalyst layer on the first region close to the anode hydrogen outlet region, thereby reducing the added amount of the anti-reverse polarity catalyst, thereby reducing the production cost of the anode catalyst layer and achieving the anti-reverse polarity effect at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 is a flow chart of a method for preparing an anode catalyst layer provided by an embodiment of the present invention;

[0030] Figure 2 This is a performance comparison diagram of a membrane electrode including a partitioned anode catalyst layer provided by an embodiment of the present invention before and after lossless reversal;

[0031] Figure 3 is a performance comparison diagram of another membrane electrode including a partitioned anode catalyst layer provided by an embodiment of the present invention before and after lossless reversal;

[0032] Figure 4 It is a performance comparison diagram of a membrane electrode including an anode anti-reverse polarity catalyst layer provided in an embodiment of the present invention before and after lossless reversal. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Proton exchange membrane fuel cells (PEMFC) have attracted much attention in the field of new energy due to their advantages such as high energy conversion efficiency, environmental friendliness, and rapid start-up at low temperatures. They have broad application prospects and development space. Among them, the membrane electrode (MEA) is the main place where the electrochemical reaction occurs and is the core component of the proton exchange membrane fuel cell. Generally speaking, the membrane electrode is mainly composed of a proton exchange membrane, a cathode / anode catalyst layer, a cathode / anode gas diffusion layer, and a sealing layer. The proton exchange membrane is located in the center of the membrane electrode, which plays the role of isolating gas, conducting protons, and blocking electrons; the catalyst layer is located on both sides of the proton exchange membrane and is the place where the electrochemical reaction occurs; the gas diffusion layer is located outside the catalyst layer and plays the role of conducting gas, draining water, and supporting.

[0035] In actual operation, due to frequent start-stop, rapid load changes, harsh operating conditions or anode flooding, the anode side of the proton exchange membrane fuel cell will be short of hydrogen, which will increase the anode potential and eventually cause reverse polarity. The occurrence of reverse polarity will cause carbon corrosion reaction in the anode catalyst layer, resulting in the fall-off of platinum particles on the surface of the carbon carrier and the collapse of the catalyst layer structure, and this phenomenon is irreversible. Therefore, in order to avoid the occurrence of reverse polarity and improve the durability of the membrane electrode, it is crucial to prepare a membrane electrode with anti-reverse polarity ability.

[0036] The current technical method for preparing anti-reverse polarity membrane electrodes is mainly to introduce water electrolysis catalysts into the anode catalyst layer: the water electrolysis catalyst is directly added to the anode slurry, stirred and dispersed, and then sprayed onto the proton exchange membrane to obtain a membrane electrode assembly material with anti-reverse polarity. However, this method does not take into account the corrosion resistance of the carbon carrier itself and the high-frequency area where the reverse polarity phenomenon occurs in the catalyst layer, resulting in excessive use of anti-reverse polarity catalysts. Although it has a certain anti-reverse polarity effect, it will lead to excessively high manufacturing costs of membrane electrodes.

[0037] Therefore, it is very necessary to provide a method for preparing an anode catalyst layer with high anti-reverse polarity ability and low cost.

[0038] An embodiment of the present application provides an anode catalyst layer, which is arranged on the anode side of the proton exchange membrane of the membrane electrode, and the anode side includes a first region and a second region; the anode catalyst layer includes a catalyst layer on the first region and a catalyst layer on the second region; the first region is close to the anode hydrogen outlet region; the second region is close to the anode hydrogen inlet region; the catalyst layer on the first region includes an anti-reverse polarity catalyst, a first platinum-based catalyst and an ionomer; the catalyst layer on the second region includes a second platinum-based catalyst and an ionomer.

[0039] Specifically, on the one hand, firstly, by partitioning the anode side, the anode side includes a first area and a second area after partitioning. The first area is close to the anode hydrogen outlet area, and the frequency of the reverse polarity phenomenon in the first area is relatively high. The reverse polarity phenomenon refers to when the anode lacks hydrogen, there is not enough hydrogen to undergo oxidation reaction to release electrons and protons to maintain charge balance. In order to maintain the charge balance of the entire stack system, other substances (such as water and carbon) in the anode catalyst layer will undergo oxidation reaction, thereby generating protons and releasing electrons. This phenomenon will cause serious corrosion of the anode catalyst, thereby causing the output performance of the hydrogen fuel cell to decay. Therefore, it is necessary to add an anti-reverse polarity catalyst to the catalyst layer on the first area. The anti-reverse polarity catalyst is a catalyst with the ability to electrolyze water, which can prevent the occurrence of carbon corrosion reaction. Adding a water electrolysis catalyst to the catalyst layer can increase the proton and electron generation rate through oxygen evolution reaction (rather than carbon oxidation reaction), actively protect the anode, and thus effectively prolong the reverse polarity time. The second area is close to the anode hydrogen inlet area. Since the frequency of the reverse polarity phenomenon in the second area is relatively low, the catalyst layer on the second area may not include an anti-reverse polarity catalyst. Thereby, the amount of anti-reverse polarity catalyst added in the catalytic layer is reduced without affecting the anti-reverse polarity capability of the membrane electrode, thereby reducing the cost of membrane electrode preparation.

[0040] On the other hand, the area ratio of the first region to the second region can be set according to specific circumstances, wherein the area of ​​the first region can be greater than the area of ​​the second region, can be equal to the area of ​​the second region, or can be smaller than the area of ​​the second region; the first region can also be further divided according to the frequency of the reverse polarity phenomenon. Exemplarily, the first region can also include a third region, a fourth region, and a fifth region, wherein the content of the anti-reverse polarity catalyst in the catalytic layer on the third region, the content of the anti-reverse polarity catalyst in the catalytic layer on the fourth region, and the content of the anti-reverse polarity catalyst in the catalytic layer on the fifth region are different, or the types of anti-reverse polarity catalysts added to the catalytic layers on the three regions are different. Exemplarily, the frequency of the reverse polarity phenomenon in the fourth region is relatively the highest among the three regions, and the anti-reverse polarity catalyst added in the catalytic layer on the fourth region has a relatively strong anti-reverse polarity ability, while the third region has a relatively high frequency of the reverse polarity phenomenon in the third region. The frequency of reverse polarity phenomenon in the region is relatively lowest, the anti-reverse polarity catalyst added in the catalytic layer on the third region has a relatively weak anti-reverse polarity ability, and the anti-reverse polarity ability of the anti-reverse polarity catalyst added in the catalytic layer on the fifth region is between the anti-reverse polarity ability of the anti-reverse polarity catalyst added in the catalytic layer on the fourth region and the anti-reverse polarity ability of the anti-reverse polarity catalyst added in the catalytic layer on the third region, which can effectively reduce the negative impact of adding the anti-reverse polarity catalyst on the performance of the catalytic layer, and is set specifically according to actual needs; and the anti-reverse polarity catalyst may not be added to the catalytic layer on the second region, or an anti-reverse polarity catalyst may be added according to actual needs, and the amount added may be much smaller than the amount of the anti-reverse polarity catalyst added in the catalytic layer on the first region, or the anti-reverse polarity ability of the added anti-reverse polarity catalyst is weaker than the anti-reverse polarity ability of the anti-reverse polarity catalyst in the catalytic layer on the first region, so as to ensure that the occurrence of reverse polarity phenomenon is completely avoided.

[0041] In the embodiment of the present application, the first platinum-based catalyst includes a platinum-based catalyst supported by a highly graphitized carbon.

[0042] Specifically, the catalytic layer on the first region adopts a platinum-based catalyst on a highly graphitized carbon carrier to enhance the stability of the carbon carrier, avoid carbon corrosion reactions, and thus improve the membrane electrode's anti-reverse polarity ability; in addition, the catalytic layer on the second region can adopt the platinum-based catalyst on a highly graphitized carbon carrier according to actual needs to ensure that the occurrence of reverse polarity phenomenon is completely avoided.

[0043] In the embodiment of the present application, the ionomer includes perfluorosulfonic acid resin.

[0044] Specifically, the sulfonic acid groups in the perfluorosulfonic acid resin can provide a proton conduction path to ensure that hydrogen ions (H +) to promote the electrochemical reaction; the perfluorosulfonic acid resin has high catalytic activity and selectivity, which can improve the overall performance of the fuel cell; the perfluorosulfonic acid resin also has high mechanical strength, which can enhance the durability and stability of the proton exchange membrane, thereby increasing the service life of the fuel cell; and the perfluorosulfonic acid resin is also a green catalyst that does not produce waste acid during use, is environmentally friendly and has sustainable development.

[0045] The present application also provides a method for preparing an anode catalyst layer. Figure 1 ,like Figure 1 As shown, the method comprises the following steps:

[0046] Step S1: providing a first raw material, wherein the first raw material comprises an anti-reverse polarity catalyst, a first platinum-based catalyst and an ionomer;

[0047] A second feedstock is provided, the second feedstock comprising a second platinum-based catalyst and an ionomer.

[0048] Specifically, the type and addition amount of the anti-reverse polarity catalyst can be set according to actual needs.

[0049] Step S2: mixing the first raw material and the first solvent to obtain a first slurry;

[0050] The second raw material and the second solvent are mixed to obtain a second slurry.

[0051] Specifically, the mixing method can be any one or more of water bath ultrasound, probe ultrasound, shearing, ball milling, and homogenization, which can be set according to actual needs; specifically, water bath ultrasound is through the cavitation effect of ultrasound in the liquid, and the generated tiny bubble nuclei quickly expand and collapse under the action of sound pressure to generate microjets, so that the particles in the liquid are constantly running-in, broken, and dispersed, and finally achieve a homogenization effect; probe ultrasound is through a probe-type design that directly applies ultrasound to the sample, which is suitable for local or specific area processing of the sample and can provide more accurate and concentrated ultrasonic energy; shearing is through the precise coordination of the rotor and the stator to form high-frequency, strong circumferential tangential velocity, angular velocity and other comprehensive kinetic energy efficiency, Under the action of the stator, the reasonably narrow gap between the stator and the rotor forms a comprehensive effect of strong, reciprocating hydraulic shear, friction, centrifugal extrusion, liquid flow collision, etc., and achieves a homogenizing effect through its physical action; ball milling is to use the grinding medium to move at high speed in a closed container to strongly impact, grind and mix the material. It is suitable for solid materials with high hardness or that need to be refined. It can effectively break large particles into small particles and mix different components at the same time; homogenization is to make the material reach a uniform state through physical or chemical methods. The homogenization technology also includes high-pressure homogenization, shear homogenization, micro-jet homogenization, etc. The specific method can be set according to actual needs. The homogenization process can improve the solubility of the substance, the reaction rate and the stability of the product. Exemplarily, a ball mill is used for high-energy ball milling of ball milling balls to mix the raw materials and the solvent so that the raw materials are evenly dispersed in the solvent.

[0052] The ratio between the mass of the raw material and the mass of the solvent is not specifically limited in the present invention and can be set according to actual needs.

[0053] Step S3: applying the first slurry to the first area to obtain a catalytic layer on the first area;

[0054] The second slurry is applied to the second area to obtain a catalytic layer on the second area.

[0055] Specifically, the coating method includes but is not limited to spraying, scraping, slit coating, sputtering, screen printing, inkjet printing, etc., which can be set according to actual needs. Exemplarily, the slurry is coated on the corresponding area by slit coating. The slit coating method is to press the slurry along the mold gap under a certain pressure and transfer it to the surface of the proton exchange membrane. By adjusting the slit width, moving speed and infusion speed of the control system, the film quality is more finely regulated, the coating thickness and uniformity are accurately controlled, the slurry is evenly distributed, and the thickness of the catalyst layer is accurately controlled, thereby preparing any one of the anode catalyst layers disclosed in the embodiments of the present application.

[0056] In the embodiment of the present application, the first solvent includes one or more combinations of water or alcohol solvents;

[0057] The second solvent includes water or an alcohol solvent or a combination thereof.

[0058] The alcohol solvent can be one or more of ethanol, isopropanol, n-propanol or other alcohols, which can be set as needed. In this application, the ratio between water and alcohol solvents is not specifically limited. It can be 100% water or 100% alcohol solvent, which can be set as needed. The solvent can adjust the fluidity and stability of the catalyst, so that the catalyst particles are dispersed, thereby affecting the performance of the catalyst layer. The interaction between the solvent and the catalyst is conducive to improving the stability of the slurry and reducing the particle size. The dispersion stability of the catalyst can also be improved by selecting the type of solvent; further affecting the structure and performance of the catalyst layer, the selection of a suitable solvent can maintain stability during the drying process of the slurry, prevent the agglomeration of catalyst particles, and thus improve the cracking of the catalyst layer.

[0059] In the embodiment of the present application, mixing the first raw material and the first solvent to obtain the first slurry includes:

[0060] The first raw material and the first solvent are mixed and then degassed to obtain a first slurry;

[0061] Mixing the second raw material and the second solvent to obtain a second slurry comprises:

[0062] The second raw material and the second solvent are mixed and then degassed to obtain a second slurry.

[0063] Specifically, the degassing treatment reduces or prevents the generation of bubbles, so that the reactant molecules can be more effectively adsorbed and reacted on the catalyst surface. The degassing process is crucial to improving the efficiency and product quality of the catalytic reaction. The generation of bubbles will affect the structure of the catalytic layer, thereby affecting the catalytic performance of the catalytic layer. The surface structure and performance of the catalytic layer are improved by degassing, so that the catalyst in the catalytic layer can better play its role. In addition, by reducing or preventing the generation of bubbles, the active sites of the catalyst in the catalytic layer can also be optimized, thereby improving the selectivity and efficiency of the catalytic reaction. Exemplarily, the slurry is degassed using a vacuum stirring degassing method, and a stirring blade is placed inside the slurry to make the bubbles at the bottom of the slurry float rapidly in a flowing state, and the bubbles are eliminated on the liquid surface, thereby achieving a degassing effect.

[0064] In the embodiment of the present application, the first slurry is applied to the first region to obtain a catalytic layer on the first region, which includes:

[0065] After applying the first slurry to the first region, heat treatment is performed to obtain a catalytic layer on the first region;

[0066] Applying the second slurry to the second region to obtain a catalytic layer on the second region includes:

[0067] After the second slurry is applied to the second region, heat treatment is performed to obtain a catalytic layer on the second region.

[0068] Specifically, the residual solvent is fully removed by heat-treating the catalyst layer, thereby avoiding the negative impact of the residual solvent on the catalyst performance, thereby improving the catalytic performance of the catalyst layer.

[0069] In an embodiment of the present application, a fuel cell is provided, comprising any anode catalyst layer disclosed in the embodiment of the present application.

[0070] The anode catalyst layer is arranged on the anode side of the proton exchange membrane of the membrane electrode, and the anode side includes a first area and a second area; the anode catalyst layer includes a catalyst layer on the first area and a catalyst layer on the second area; the first area is close to the anode hydrogen outlet area; the second area is close to the anode hydrogen inlet area; wherein the catalyst layer on the first area includes an anti-reverse polarity catalyst, a first platinum-based catalyst and an ionomer; the catalyst layer on the second area includes a second platinum-based catalyst and an ionomer; specifically, the first platinum-based catalyst includes a highly graphitized carbon carrier platinum-based catalyst; the ionomer includes a perfluorosulfonic acid resin, and the second platinum-based catalyst generally uses a conventional carbon carrier platinum-based catalyst; the present invention has no special requirements for the preparation of other parts of the membrane electrode, and a conventional membrane electrode preparation method in the art can be adopted. The specific preparation process is well known in the membrane electrode field and will not be repeated here; the membrane electrode containing any anode catalyst layer disclosed in the embodiments of the present application achieves the avoidance of the irreversible phenomenon caused by the carbon corrosion reaction caused by the reverse polarity phenomenon, which leads to the shedding of platinum particles on the surface of the carbon carrier and the collapse of the catalyst layer structure, thereby improving the durability of the membrane electrode.

[0071] In an embodiment of the present application, a fuel cell is provided, comprising a membrane electrode disclosed in an embodiment of the present application.

[0072] The present invention has no special requirements for the preparation of the battery, and a conventional method for preparing a fuel cell in the art can be used. The specific preparation process is well known in the field of fuel cells and will not be described in detail here. Exemplarily, the membrane electrode with anti-reverse polarity capability prepared in the embodiment of the present application is assembled into a fixture to form a single cell, and the cell also has anti-reverse polarity capability, thereby increasing the service life of the battery. The present invention has no special requirements for the preparation of the battery, and a conventional method for preparing a battery in the art can be used. The specific preparation process is well known in the field of batteries and will not be described in detail here.

[0073] The present invention will be described in detail below through examples.

[0074] Example 1

[0075] This embodiment is used to illustrate the anode catalyst layer and its preparation method, membrane electrode and fuel cell of the present invention.

[0076] Preparation of the first slurry: Weigh 1.5g of a highly graphitized carbon carrier platinum-based catalyst, 0.78g of Japan Tanaka Precious Metals (TKK) IrOx (x represents the number of oxygen atoms) anti-reverse polarity catalyst, 4.5g of 20% perfluorosulfonic acid resin solution, 12.8g of ultrapure water, and 12.2g of n-propanol; add ultrapure water to the above two catalysts, add n-propanol after fully wetting, and then add the perfluorosulfonic acid resin solution for pre-dispersion; disperse the first slurry through a ball mill, wherein the rotation speed is 300rpm and the dispersion time is 4h. After the ball milling dispersion is completed, the first slurry is degassed to obtain the final first slurry.

[0077] Apply the first slurry to the first area to obtain a catalytic layer on the first area: Apply the first slurry to the anode side of the proton exchange membrane with the cathode catalytic layer, i.e., the first area, near the hydrogen outlet, by doctor blade coating, and dry it by heat treatment to obtain a catalytic layer on the first area. The Pt loading of the catalytic layer on the first area is 0.05 mg / cm 2 , Ir loading is 0.03 mg / cm 2 , and the thickness of the catalytic layer on the first region is 4 μm.

[0078] Preparation of the second slurry: weigh 2.0 g of carbon carrier platinum-based catalyst, 6.0 g of 20% perfluorosulfonic acid resin solution, 12.4 g of ultrapure water, and 11.6 g of n-propanol; add ultrapure water to the above catalyst, add n-propanol after fully moistening, and then add perfluorosulfonic acid resin solution for pre-dispersion; disperse the slurry through a ball mill, wherein the rotation speed is 300 rpm and the dispersion time is 4 hours. After the ball mill dispersion is completed, degassing treatment is carried out to obtain the second slurry.

[0079] The second slurry is applied to the second area to obtain a catalytic layer on the second area: the second slurry is applied to the uncoated area near the hydrogen inlet on the other side of the proton exchange membrane with the cathode catalytic layer by doctor blade coating, and dried by heat treatment to form a catalytic layer on the second area. The Pt loading of the catalytic layer on the second area is 0.07 mg / cm 2 , the thickness of the catalytic layer on the second region is 4 μm.

[0080] Membrane electrode and single cell assembly: The prepared catalyst layer and proton exchange membrane are hot-pressed with the gas diffusion layer and frame to form a membrane electrode, and then the membrane electrode is assembled into a fixture to form a single cell.

[0081] Reverse polarity resistance test: After the membrane electrode is fully activated, a polarization curve test is performed to obtain the initial performance of the membrane electrode; then a non-destructive reverse polarity test is performed for 45 minutes, after which the membrane electrode after reverse polarity is fully activated again and a polarization curve test is performed to obtain the performance of the membrane electrode after reverse polarity; for the comparison of the performance before and after non-destructive reverse polarity, please refer to Figure 2 , Figure 2 This is a performance comparison chart of a membrane electrode containing a partitioned anode catalyst layer before and after lossless reversal.

[0082] Example 2

[0083] This embodiment is used to illustrate the anode catalyst layer and its preparation method, membrane electrode and fuel cell of the present invention.

[0084] Preparation of the first slurry: weigh 1.5g of highly graphitized carbon carrier platinum-based catalyst, 0.62g of Japan Tanaka Precious Metals (TKK) IrOx anti-reverse polarity catalyst, 4.5g of 20% perfluorosulfonic acid resin solution, 12.1g of ultrapure water, and 13.6g of n-propanol; add ultrapure water to the above two catalysts, add n-propanol after fully wetting, and then add perfluorosulfonic acid resin solution for pre-dispersion; disperse the slurry through a ball mill at a speed of 300rpm and a dispersion time of 4h. After the ball mill dispersion is completed, the slurry is degassed to obtain the final first slurry.

[0085] Apply the first slurry to the first area to obtain a catalytic layer on the first area: Apply the first slurry to the other side of the proton exchange membrane with the cathode catalytic layer near the hydrogen outlet, i.e., the first area, by doctor blade coating, and dry to form a catalytic layer on the first area. The Pt loading of the catalytic layer on the first area is 0.05 mg / cm 2 , Ir loading is 0.02 mg / cm 2 , the thickness of the catalytic layer on the first region is 4 μm.

[0086] Preparation of the second slurry: weigh 2.0 g of carbon carrier platinum-based catalyst, 6.0 g of 20% perfluorosulfonic acid resin solution, 12.4 g of ultrapure water, and 11.6 g of n-propanol; add ultrapure water to the above catalyst, add n-propanol after fully moistening, and then add perfluorosulfonic acid resin solution for pre-dispersion; disperse the slurry through a ball mill at a speed of 300 rpm for 4 hours. After the ball milling dispersion is completed, the slurry is degassed to obtain the final second slurry.

[0087] The second slurry is applied to the second area to obtain a catalytic layer on the second area: the second slurry is applied to the uncoated area near the hydrogen inlet on the other side of the proton exchange membrane with the cathode catalytic layer by blade coating, and dried by heat treatment to form a catalytic layer on the second area. The Pt loading of the catalytic layer on the second area is 0.07 mg / cm 2 , the thickness of the catalytic layer on the second area is 4μm.

[0088] Membrane electrode and single cell assembly: The prepared CCM (catalyst coated proton membrane, which is prepared by coating the fuel cell catalyst on both sides of the proton exchange membrane) is hot-pressed with the gas diffusion layer and the frame to form a membrane electrode, and then the membrane electrode is assembled into a fixture to form a single cell.

[0089] Reverse polarity resistance test: After the membrane electrode is fully activated, a polarization curve test is performed to obtain the initial performance of the membrane electrode; then a non-destructive reverse polarity test is performed for 45 minutes, after which the membrane electrode after reverse polarity is fully activated again and a polarization curve test is performed to obtain the performance of the membrane electrode after reverse polarity. For a comparison of the performance before and after non-destructive reverse polarity, please refer to Figure 3 , Figure 3 This is a performance comparison chart of another membrane electrode containing a partitioned anode catalyst layer before and after lossless reversal.

[0090] Comparative Example 1

[0091] Preparation of the first slurry: weigh 2g of highly graphitized carbon carrier platinum-based catalyst, 1.04g of Japan Tanaka Precious Metals (TKK) IrOx anti-reverse polarity catalyst, 6g of 20% perfluorosulfonic acid resin solution, 17.1g of ultrapure water, and 16.3g of n-propanol; add ultrapure water to the above two catalysts, add n-propanol after fully wetting, and then add perfluorosulfonic acid resin solution for pre-dispersion; disperse the first slurry through a ball mill at a speed of 300rpm and a dispersion time of 4h. After the ball milling dispersion is completed, the first slurry is degassed to obtain the final first slurry.

[0092] The first slurry is applied to the anode side to obtain an anode catalyst layer: the first slurry is applied to the other side of the proton exchange membrane with the cathode catalyst layer, i.e., the anode side, by doctor blade coating, and dried by heat treatment to form an anode anti-reverse polarity catalyst layer. The Pt loading of the anode anti-reverse polarity catalyst layer is 0.05 mg / cm 2 , Ir loading is 0.04 mg / cm 2 The thickness of the anode anti-reverse polarity catalyst layer is 4 μm.

[0093] Membrane electrode and single cell assembly: The prepared CCM is hot-pressed with the gas diffusion layer and the frame to form a membrane electrode, and then the membrane electrode is assembled into a fixture to form a single cell.

[0094] Reverse polarity resistance test: After the membrane electrode is fully activated, a polarization curve test is performed to obtain the initial performance of the membrane electrode; then a non-destructive reverse polarity test is performed for 45 minutes, after which the membrane electrode after reverse polarity is fully activated again and a polarization curve test is performed to obtain the performance of the membrane electrode after reverse polarity. For a comparison of the performance before and after non-destructive reverse polarity, please refer to Figure 4 , Figure 4 This is a performance comparison chart of a membrane electrode including an anode anti-reverse catalyst layer before and after lossless reversal.

[0095] It can be known from the above technical scheme of the embodiment of the present invention that the present invention discloses an anode catalyst layer, which is arranged on the anode side of the proton exchange membrane of the membrane electrode, and the anode side includes a first region and a second region; the anode catalyst layer includes a catalyst layer on the first region and a catalyst layer on the second region; the first region is close to the anode hydrogen outlet region; the second region is close to the anode hydrogen inlet region; the catalyst layer on the first region includes an anti-reverse polarity catalyst, a first platinum-based catalyst and an ionomer; the catalyst layer on the second region includes a second platinum-based catalyst and an ionomer; the present invention divides the anode catalyst layer according to the region close to the anode hydrogen outlet region or the region close to the anode hydrogen inlet region, and the anode catalyst layer includes a catalyst layer on the first region and a catalyst layer on the second region; wherein, the anti-reverse polarity catalyst is added only to the catalyst layer on the first region close to the anode hydrogen outlet region, which achieves the anti-reverse polarity effect while reducing the amount of anti-reverse polarity catalyst added, thereby reducing the production cost of the anode catalyst layer, improving the durability of the membrane electrode based on the catalyst layer, and thereby extending the service life of the fuel cell based on the membrane electrode.

[0096] The above description has fully disclosed the specific embodiments of the present invention. It should be pointed out that any changes made by those skilled in the art to the specific embodiments of the present invention do not deviate from the scope of the claims of the present invention. Accordingly, the scope of the claims of the present invention is not limited to the above specific embodiments.

Claims

1. An anode catalyst layer, characterized in that: The anode catalyst layer is arranged on the anode side of the proton exchange membrane of the membrane electrode, and the anode side includes a first region and a second region; the anode catalyst layer includes a catalyst layer on the first region and a catalyst layer on the second region; the first region is close to the anode hydrogen outlet region; the second region is close to the anode hydrogen inlet region; the catalyst layer on the first region includes an anti-reverse polarity catalyst, a first platinum-based catalyst and an ionomer; the catalyst layer on the second region includes a second platinum-based catalyst and an ionomer.

2. The anode catalyst layer according to claim 1, characterized in that: The first platinum-based catalyst comprises a highly graphitized carbon-supported platinum-based catalyst.

3. The anode catalyst layer according to claim 1, characterized in that: The ionomer includes a perfluorosulfonic acid resin.

4. A method for preparing the anode catalyst layer according to any one of claims 1 to 3, characterized in that: The method comprises: Providing a first raw material, wherein the first raw material includes the anti-reverse polarity catalyst, the first platinum-based catalyst and the ionomer; providing a second feedstock, the second feedstock comprising the second platinum-based catalyst and the ionomer; Mixing the first raw material and the first solvent to obtain a first slurry; Mixing the second raw material and the second solvent to obtain a second slurry; Applying a first slurry to a first region to obtain a catalytic layer on the first region; The second slurry is applied to the second region to obtain a catalytic layer on the second region.

5. A preparation method according to claim 4, characterized in that: The first solvent includes one or more combinations of water or alcohol solvents; The second solvent includes water or one or more combinations of alcohol solvents.

6. A preparation method according to claim 4, characterized in that: The mixing method includes one of water bath ultrasound, probe ultrasound, shearing, ball milling or homogenization.

7. A preparation method according to claim 4, characterized in that: The mixing of the first raw material and the first solvent to obtain a first slurry comprises: The first raw material and the first solvent are mixed and then degassed to obtain a first slurry; The mixing of the second raw material and the second solvent to obtain a second slurry comprises: The second raw material and the second solvent are mixed and then degassed to obtain a second slurry.

8. A preparation method according to claim 4, characterized in that: The step of applying the first slurry to the first region to obtain a catalytic layer on the first region comprises: After applying the first slurry to the first region, heat treatment is performed to obtain a catalytic layer on the first region; The step of applying the second slurry to the second region to obtain a catalytic layer on the second region comprises: After the second slurry is applied to the second region, heat treatment is performed to obtain a catalytic layer on the second region.

9. A membrane electrode, characterized in that: The invention comprises an anode catalyst layer according to any one of claims 1 to 3.

10. A fuel cell, characterized in that: It comprises a membrane electrode as described in claim 9.